Islamic Education of the 21th Century and Its Implications in the Building of Civilization - Muhammad Talhah Ajmain@Jima’ain, Khadijah Abdul Razak, Wan Abdul Rahman Wan Ibrisam Fikry, Mohamad Anas Mohamad Yaakub, Ahmad Syafiq Yusof, Muhammad Aiman Abdull Rahim (International Journal of Advanced Science and Technology, 2020)
Education is a necessity in the form of Individuals that eventually happens to a generation that will develop a great Civilization. A Civilization that is developing is closely linked to the current environment of Technology in the 21st century. Islamic education contributes to the building of character and personality so that individuals within the civilization can build a great civilization without ignoring the challenges that must be faced in the 21st Century. The Industrial Revolution 4.0 (IR 4.0) was present to assist in providing various options for the use of media and electronic technology tools to facilitate communication such as in the field of education in the face of the current Covid19 outbreak. Thus, this conceptual paper using qualitative methodology based on scientific references and libraries, will shed light on the elusive forms of Islamic education in interacting with the electronic media to meet the challenges of the 21st century and their impact on the construction of Civilization.Keywords: Islamic education, 21st century, technology, civilization.